Improvement of Multi-criteria Evaluation Tools by AHP-ELECTRE II Hybridization: Application to Drilling - Ouedraogo, Nabonswendé Macaire; Savadogo, Zoïnabo; Gouba, Elisée (European Journal of Applied Sciences, 2025)
Elimination and Reality Choices (ELECTRE II) and Hierarchical Decision Process Analysis (HDPA) methods are widely used in decision support. Although they are effective in many cases, they are not without their limitations. The AHP method is sometimes considered to be compensatory. As for the ELECTRE II method, it lacks rigorous tools for setting the weights of the decision criteria. To overcome these limitations, we have developed a hybrid method, AHP-ELECTRE II, which combines these two approaches. This AHP-ELECTRE II hybrid combines the advantages of both methods. In this way, we have been able to put in place a procedure that allows criteria to be weighted appropriately using the technique of binary comparison between criteria in accordance with the requirements of the AHP method. This comparison is made by the decision-maker, enabling him to determine the relative weights of the criteria objectively. We then used the weights of the criteria obtained to aggregate performance using the ELECTRE II method. This enabled us to deal with the interactions between the criteria and to rank the alternatives according to how well they met the criteria defined. In our study, we applied this hybrid method to didactic problems, which enabled us to obtain satisfactory results by taking better account of the decision-maker’s preferences. We used it to evaluate areas suitable for drilling, simultaneously taking into account indicators of accessibility, potential and exploitable water.The advantage of this hybrid approach is that it combines the analytical rigour of AHP with ELECTRE II’s ability to handle interactions between criteria, providing a more complete method that is suited to complex multi-criteria decision support problems.